If You Build It Nearby and Keep the Price Low, Will They Come? Large‐Scale Evidence on the Relative Roles of Access and Quality in Use of Healthcare in Low‐and Middle‐Income Countries. (3rd February 2020) - Wilson, Nicholas
Abstract: Health policy reform often emphasises improving access to healthcare. Recent studies highlight the role healthcare quality plays in determining which health providers individuals use and health outcomes. Yet, there is little standardised large‐scale evidence on the importance of quality of care relative to access in determining healthcare use. This paper examines the relative roles of access and quality in whether individuals seek healthcare and how these vary with socioeconomic status in a sample of over 250, 000 national household survey respondents from low‐ and middle‐income countries. My results suggest that quality is as large a barrier as access. Among quality barriers, drug availability is as large a barrier as provider availability. Analyses of the barriers‐socioeconomic status gradients indicate that the quality‐SES gradient is much less steep than the access‐SES gradient, highlighting that increasing incomes may not be sufficient to address quality barriers and that supply‐side interventions may be necessary.